The Impact of Oil Price Shocks on Stock Market Returns in Each Regime using Vector Autoregressive Method - Wahida Ainun Mumtaza; Asep Saefuddin; Bagus Sartono (Xplore: Journal of Statistics, 2019)
World oil prices affect the stock market in developed and developing countries, including Indonesia. Therefore, development of the Indonesian economy is affected by the shocks of world oil prices and the stock market. This study characterized the impact and causal relationship between oil price shocks and stock market in Indonesia from 1996 to 2016. In this research, there are nine sectors of the stock market, there are sector agriculture, basic, consumer, finance, infrastructure, mining, miscellaneous industry, property, and trade. To analyze the impact of oil price shocks to Indonesia stock market, we employed an autoregressive vector model (VAR) methodology involving different lags for each regime. We examined that the dynamic relationship between changes in oil prices and stock market in Indonesia in each regime varied which was indicated by impulse response and variance decomposition value. The Granger Causality test found that there were one-way relationship between oil variable with infrastructure sector variable, oil variable with agricultural sector variable and oil variable with basic sector variable in Regime 2, Regime 3 there was one way relationship significantly between oil variable with infrastructure sector variable and Regime 4 also there were one-way relationship. One-way relationship significantly between oil variable with property sector variable, but not significant in Regime 1.